2019
DOI: 10.1016/j.jebo.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Do political risks harm development of oil fields?

Abstract: We examine the impact of political risks and financial development on investments in the petroleum industry utilizing a unique dataset of investments in individual oil and gas fields around the world. We find that the expected time to investment is shorter in countries that are politically stable, have solid property rights protection and more developed financial systems. Political risks have the strongest impact on multinational companies, whereas financial development matters only for domestic national oil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Similarly, Bøe et al studied the effect of political risks and financial growth on investment in the oil industry and found that it takes a shorter expected time for investment in countries with political stability, strong property rights protection and more developed financial methods [64]. At the firm level, they found a shorter expected time for investment for firms with a higher valuation and lower debts.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Bøe et al studied the effect of political risks and financial growth on investment in the oil industry and found that it takes a shorter expected time for investment in countries with political stability, strong property rights protection and more developed financial methods [64]. At the firm level, they found a shorter expected time for investment for firms with a higher valuation and lower debts.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Horn et al validated this as they found that decision makers in the energy sector often use advanced systems for appraising investment [65]. As far as Bøe et al are concerned, there are no studies analyzing the effects of financial development on oil investment and there are only two, which are based on micro-level data, which examine the influence of political stability on oil investments [64].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For overseas oil and gas investment projects, the most significant elements include a long life cycle, great uncertainty, high capital requirement, and irreversibility of the investments (Chapman and Ward, 2004). Due to the decade-long life cycles of such projects, they are exposed to a multitude of risk factors including the political environment of the resource countries (Bøe et al, 2019), economic conditions (Ma et al, 2020), cultural factors, religious factors (Weldegiorgis et al, 2017), as well as geological conditions (Asrilhant et al, 2007) and oil price risks (Chorn and Shokhor, 2006). Because of the intra relevance and complexity of risk management, the identification of risks is usually decided by managers and experts.…”
Section: Introductionmentioning
confidence: 99%
“…Oil and gas exploration and field development have been subject to economic research for decades. In the existing literature, the main focus has been on the US and UK oil and gas data sets, because international data sets provide much less detailed information (Bøe et al, 2018). In this paper, we investigate the relation between investment activity and economic and field-specific variables on the Norwegian Continental Shelf from 1967 to 2015.…”
Section: Introductionmentioning
confidence: 99%